Kunstwoche Dillingen : 14 Tage aktuelle Kunst. - Kunstverein Dillingen (Dillingen : Kunstverein Dillingen, 1988)
Butz, Heinz ; Schäuffelen, Konrad Balder ; Hopf, Reinhilde ; Wirsching, Georg ; Rainer, Arnulf ; Schmidt, Pavel ; Renner, Paul ; Lassnig, Maria ; Heenes, Jockel ; Jurkowitsch ; Alois ; Sagerer, Alexeij ; Müller, Cornelie ; Kühnel, Wolfgang ; Thomas, Agelika ; Wirsching, Georg
Kunstwoche Dillingen : 14 Tage aktuelle Kunst, Kunstverein Dillingen, 16. Sept. mit 2. Okt. 1988
boek